Development of glutamic acid and fluorine-based ionic liquid for solid scale dissolution - Adam, Fatmawati; Hassan, Zulkafli Bin; Abdullah, Norhayati; Ridzuan, Norida (2018)
This report presents the study of amino acid-based ionic liquid as scale dissolver in well stimulation as well as the blending formulation of solid scale dissolver. Scales have been a major problem in the oil and gas industries. Problems with scales cost the industries millions of dollars in damage and loss of production. Scales usually occur at the wellbore, oil pipelines, and other production facilities. Scales need to be controlled since the effects of the production lost and cost management cost is massive. Precipitation of scales contributes to equipment wear, corrosion and flow restriction which then lead to decreasing in oil and gas production. The aim of this study is to synthesise glutamic acid based ionic liquid incorporated with fluorine as an alternative scale inhibitor and control in well stimulation. The targeted scales are Calcite (CaCO3) and Barite (BaSO4). The second objective is to evaluate the ionic liquid for dissolution test of solid scale and finally to develop a preliminary blending formulation of solid scale dissolver targeting barite scale. In this study, two commercial ionic liquids were used to evaluate the potential of ionic liquid in solid scale dissolution. New amino acid ionic liquid (AAIL) based from glutamic was synthesized and evaluated to determine its ability as a scale dissolver. The dissolution of solid scales was determined by using dissolution test utilizing the gravimetric method and elemental analysis using inductively coupled plasma optical emission spectrometry (ICP-OES).